Pengaruh Pendidikan Kewirausahaan Terhadap Niat Berwirausaha Dan Dampaknya Terhadap Kemiskinan Multidimensi - Faiz Bahalwan; Novita Sari; Imroatus Sakinah; Siti Sri Wulandari; Yessy Artanti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study is to determine the influence between Integrated Entrepreneurship Education (IEE) and Multidimensional Poverty Alleviation (MPA), Integrated Entrepreneurship Education (IEE) and Entrepreneurial Intention (EI), Entrepreneurial Intention (EI) and Multidimensional Poverty Alleviation (MPA), Integrated Entrepreneurship Education (IEE), Multidimensional Poverty Alleviation (MPA) and Entrepreneurial Intention (EI)